The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/ejoc.200500533
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Spin Interactions Across the “Cove” in the (Z) and (E) Isomers of 1,1′‐Difluoro‐9,9′‐bifluorenylidene

Abstract: In the (Z) isomer, but not in the (E) isomer of title compound 1, moderate 19F,19F spin–spin coupling across the “cove” is observed [J(F,F) = 11.0 Hz], which is deemed to obey a through‐space mechanism. The coupling between the isochronous fluorine nuclei of 1Z causes second‐order effects in the 1H, 13C and 19F NMR spectra of this compound and allows its easy distinction from the (E) isomer. A B3LYP/6‐31+G(d) calculation of 1Z as an isolated molecule was carried out which gave a non‐bonded F,F distance d(F,F) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Table 2 gives the relative energies of a series of homodesmotic reactions of the studied BFs. Table 3 gives representative optimized geometrical parameters of the twisted conformations of the various BFs under study [at the B3LYP/ 6-311++G(d,p) level] and the respective experimental parameters of Z11ЈF2, [24] Z11ЈCl2, [31] and 1,3,6,8,1Ј,3Ј,6Ј,8Ј-octachlorobifluorenylidene (13681Ј3Ј6Ј8ЈCl8) [26] derived from their molecular (X-ray) structures. The following geometrical parameters were included: pure ethylenic twist angle [4] (ω) around C 9 =C 9Ј , defined as the average of the two torsion angles C 9a -C 9 -C 9Ј -C 9aЈ and C 8a -C 9 -C 9Ј -C 8aЈ ; folding dihedral angle of the tricyclic (fluorenylidene) moiety (A-B), defined as the dihedral angle between the leastsquare planes of the atoms C 1 , C 2 , C 3 , C 4 , C 4a , C 9a and C 5 , C 6 , C 7 , C 8 , C 8a , C 4b ( Figure 2) of the benzene rings and reflecting the nonplanarity of the tricyclic moieties; twisting dihedral angle between the fluorenylidene moieties (AEB-CFD), defined as the dihedral angle between the leastsquare planes of all the untagged and all the tagged carbon atoms; pyramidalization angles [4] (χ) at C 9 and C 9Ј , defined as the improper torsion angle C 9a -C 9 -C 9Ј -C 8a subtracted from 180°, bond lengths r(…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 2 gives the relative energies of a series of homodesmotic reactions of the studied BFs. Table 3 gives representative optimized geometrical parameters of the twisted conformations of the various BFs under study [at the B3LYP/ 6-311++G(d,p) level] and the respective experimental parameters of Z11ЈF2, [24] Z11ЈCl2, [31] and 1,3,6,8,1Ј,3Ј,6Ј,8Ј-octachlorobifluorenylidene (13681Ј3Ј6Ј8ЈCl8) [26] derived from their molecular (X-ray) structures. The following geometrical parameters were included: pure ethylenic twist angle [4] (ω) around C 9 =C 9Ј , defined as the average of the two torsion angles C 9a -C 9 -C 9Ј -C 9aЈ and C 8a -C 9 -C 9Ј -C 8aЈ ; folding dihedral angle of the tricyclic (fluorenylidene) moiety (A-B), defined as the dihedral angle between the leastsquare planes of the atoms C 1 , C 2 , C 3 , C 4 , C 4a , C 9a and C 5 , C 6 , C 7 , C 8 , C 8a , C 4b ( Figure 2) of the benzene rings and reflecting the nonplanarity of the tricyclic moieties; twisting dihedral angle between the fluorenylidene moieties (AEB-CFD), defined as the dihedral angle between the leastsquare planes of all the untagged and all the tagged carbon atoms; pyramidalization angles [4] (χ) at C 9 and C 9Ј , defined as the improper torsion angle C 9a -C 9 -C 9Ј -C 8a subtracted from 180°, bond lengths r(…”
Section: Resultsmentioning
confidence: 99%
“…Kresmar et al, [24] on the basis of analysis of the 1 H NMR spectrum, reported 11.0 Hz for the 7 J F-F coupling, but did not report the details of the 19 F spectrum. The 13 C data differ slightly from ours, with Kresmar reporting 1 J C-F = 260.2 Hz for E11ЈF2 and 265.2 or 255.5 Hz for Z11ЈF2, compared to our value of 262.3 Hz.…”
Section: Through-space Interactions In Z11јf2mentioning
confidence: 97%
See 3 more Smart Citations